The Martians have landed! a history of media-driven panics and hoaxes - Bartholomew, Robert E. (McFarland & Co., 2012)
"This book presents more than three dozen studies of media scares from the 17th to the 21st century, including hoaxes perpetrated via newspapers, radio, television and cyberspace. It explores hoaxes that highlight the impact of the media on our lives and its tendency to sensationalize. Several cases are global in scope, revealing the the power global media wields"--Provided by publisher.